NILAI MORAL DALAM NOVEL KAU, AKU, DAN SEPUCUK ANGPAU MERAH KARYA TERE LIYE - Sainil Amral; Maya Anjelina (Universitas Batanghari, 2023)
This study aims to describe the moral values in the novel Kau, Aku, Dan Sepucuk Angpau Merah by Tere Liye (Content Analysis Study) which refers to 6 aspects of moral values of human relations with fellow humans including, positive thinking, helping others, love, helping the weak selflessly, knowing each other, and respecting each other. This research uses descriptive qualitative research. The data used in this research are primary data and secondary data. Primary data is a fact that can be used as material for research, namely from dialog, narration, and events that contain moral values contained in the novel Kau, Aku, Dan Sepucuk Angpau Merah by Tere Liye. Based on the results of research and discussion, it can be concluded that the moral values in the novel Kau, Aku, Dan Sepucuk Angpau Merah by Tere Liye, there are moral values of positive thinking aspects as many as 45 quotations, aspects of helping others as many as 22 quotations, love as many as 48 quotations, helping the weak selflessly as many as 6 quotations, knowing each other as many as 11 quotations, respecting each other as many as 26 quotations. From the six aspects of moral values, a total of 158 quotations were collected. The most dominant moral value found is the moral value of positive thinking and love. Thus, the novel Kau, Aku, dan Sepucuk Angpau Merah by Tere Liye is inspired by the basic thoughts of positive thinking and love.